Influence of Mo doping on mercury capture and SO2 tolerance of MoxFe6Mn1-xOy magnetic sorbent. (15th January 2022) - Zhou, Qiang; Di, Guancheng; Tao, Xin; Song, Tao; Lu, Ping; Xu, Guiling; Dong, Liang
Highlights: Mo0.2 Fe6 Mn0.8 Oy is a promising magnetic mercury sorbent with high SO2 tolerance. Mo doping modifies the pore channel and uniformly disperses the Mn 4+ active sites. Mo doping improve SO2 tolerance of sorbent due to a larger affinity of Mo to sulfur. SO2 in flue gas inhibits the mercury capture and promotes part of Hg2 SO4 formation. Abstract: Molybdenum (Mo) was doped to Fe-Mn magnetic sorbent (named Mox Fe6 Mn1-x Oy ) through co-precipitation method to enhance the SO2 tolerance for mercury capture. The influence of Mo doping on mercury capture and SO2 tolerance of Mox Fe6 Mn1-x Oy sorbent was studied in a fixed-bed experimental device. Temperature programmed mercury desorption (Hg-TPD) test was also conducted to analyze the mercury capture product on the used sorbent. Combing with sorbent characterization, the mechanism of mercury capture and resistance to SO2 poisoning of Mox Fe6 Mn1-x Oy sorbent was explored. The results show that the magnetic Mo0.2 Fe6 Mn0.8 Oy sorbent is an excellent mercury capture sorbent with high SO2 tolerance. O2 co-existence with SO2 weakens the inhibition from SO2 on mercury capture, but H2 O intensifies SO2 poisoning. Mo existing in Mo0.2 Fe6 Mn0.8 Oy sorbent is not active sites for mercury capture, but Mo doping modifies the pore channel and uniformly disperses the Mn 4+ active sites. Mo doping can also promote the oxidation of SO2 to SO3, which is beneficial to mercury capture. More importantly, after Mo doping, the SO2 tolerance of Mo0.2 Fe6 Mn0.8 Oy sorbent is significantly improved because of a lager affinity of sulfur to Mo. The Hg-TPD test indicates that HgO is the main mercury capture product. Therefore, it can be determined that most of Hg 0 is adsorbed on MnO2 in Mo0.2 Fe6 Mn0.8 Oy via Mars-Maessen mechanism. The existence of SO2 promotes part of Hg2 SO4 formation and the co-existence of H2 O leads to more Hg2 SO4 formation.